1992
DOI: 10.1002/ana.410320410
|View full text |Cite
|
Sign up to set email alerts
|

Calbindin‐D28K in the basal ganglia of patients with parkinsonism

Abstract: An immunohistochemical study was carried out to investigate the topographic distribution of calbindin-D28k in the human basal ganglia and substantia nigra and its alterations in patients with idiopathic Parkinson's disease (PD), parkinsonism-dementia complex on Guam, progressive supranuclear palsy, and striatonigral degeneration. In normal control subjects, calbindin-D28k immunoreactivity was identified in the medium-sized neurons and neuropil of the matrix compartment of the striatum, the woolly fiber arrange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 38 publications
1
36
0
Order By: Relevance
“…A ventral-to-dorsal gradient of intensity of calbindin immunostaining in the striatum has been described in monkeys, cats, rats, and humans Ito et al, 1992;De Las Heras et al, 1994;Francois et al, 1994). A similar ventral-to-dorsal gradient in immunostaining intensity has been described for SP and enkephalin immunoreactivities in the human striatum (Graybiel and Ragsdale, 1983;Ito et al, 1992;Kowall et al, 1993).…”
Section: Comparisons With Other Studiesmentioning
confidence: 61%
See 1 more Smart Citation
“…A ventral-to-dorsal gradient of intensity of calbindin immunostaining in the striatum has been described in monkeys, cats, rats, and humans Ito et al, 1992;De Las Heras et al, 1994;Francois et al, 1994). A similar ventral-to-dorsal gradient in immunostaining intensity has been described for SP and enkephalin immunoreactivities in the human striatum (Graybiel and Ragsdale, 1983;Ito et al, 1992;Kowall et al, 1993).…”
Section: Comparisons With Other Studiesmentioning
confidence: 61%
“…Ito et al (1992) found that calbindin and enkephalin immunoreactivities have similar distribution patterns in the ventral striatum of the human. Hurd and Herkenham (1995) found that AChE-poor zones corresponded to mu opiate receptor-rich zones in much of the human striatum but not in the nucleus accumbens.…”
Section: Comparisons With Other Studiesmentioning
confidence: 88%
“…However, there are reasons to doubt whether this type of cellular stress alone is responsible for PD pathology. For example, there is considerable regional variability in the vulnerability of DA neurons in PD, with some DA neurons in the brain being devoid of pathology (19,(21)(22)(23)(24). Moreover, many of the neurons showing signs of pathology in PD do not use DA as a transmitter (e.g.…”
Section: The At-risk Neuronal Phenotypementioning
confidence: 99%
“…However, there are reasons to doubt whether this type of cellular stress alone is responsible for the loss of DA neurons in PD. For example, there is considerable regional variability in the vulnerability of DA neurons in PD, with some areas being devoid of pathological markers (Matzuk and Saper 1985;Kish et al 1988;Saper et al 1991;Ito et al 1992;Damier et al 1999). Moreover, Ldopa administration (which relieves symptoms by elevating DA levels in PD patients) does not accelerate disease progression (Fahn 2005), suggesting that DA itself is not a significant source of reactive oxidative stress, at least in the short term.…”
Section: Physiological Features Of Neurons At High Risk In Pdmentioning
confidence: 99%